ISLAMIC LEADERSHIP, WORK MOTIVATION, AND EMPLOYEE PERFORMANCE OF BANK JATIM SYARIAH SURABAYA - Amaliyah, Hafidhotul; Fahrullah, A'rasy (Journal Intellectual Sufism Research (JISR), 2020)
This study aims to determine the positive and simultaneous influence between Islamic leadership and work motivation on the performance of employees of Bank Jatim Syariah Surabaya Branch Office. The research method used is quantitative with an associative approach. The selection of research subjects using the method Probably sampling with simple random sampling is random sampling from the population. Data collection techniques using a questionnaire and measured with a Likert scale and then processed and analyzed with the IBM SPSS Statistics application. Based on the results of the analysis shows that Islamic leadership has a significant effect on performance, and work motivation also has a significant effect on employee performance, and Islamic leadership and work motivation simultaneously have a significant effect on employee performance. And the value of R. Square is equal to 0.480 so that means that the simultaneous influence between variable X with Y variable is 48%.